An attempt to provide new services to the repository network in the UK: the UK RepositoryNet+ Project - De-Castro, Pablo (Anuario ThinkEPI, 2014)
The JISC-funded UK RepositoryNet+ (aka RepNet) project aims to build a socio-technical infrastructure for enhancing the institutional repository network at UK Higher Education institutions. The RepNet ran from Aug´2011 to Jul´2013 in its project stage, and has now been extended two years (undergoing a name change along the way), during which it aims to become a new service. So far, the RepNet has brought together existing repository projects and/or services under a common umbrella and has devised an ITIL-based workflow for actually turning repository projects into new repository services. This note describes the different repository working areas the RepNet has identified, the services it covers and the pending work.